Building-integrated trigeneration system: Energy, environmental and economic dynamic performance assessment for Italian residential applications. (February 2017) - Sibilio, Sergio; Rosato, Antonio; Ciampi, Giovanni; Scorpio, Michelangelo; Akisawa, Atsushi
Abstract: A trigeneration system uses only one source of primary energy, while providing power, heating and cooling simultaneously. This primary source can be represented by either fossil fuels or some appropriate renewable energy sources (biomass, biogas, solar energy, etc.). In this paper a brief review of micro-trigeneration systems for residential applications was reported. An innovative building-integrated micro-trigeneration system was proposed. This proposed system was based on a natural gas-fueled internal combustion engine micro-cogeneration unit for heating purposes and domestic hot water production. The cogeneration device fed an electric air-cooled vapor compression water chiller for cooling purposes. The micro-trigeneration system was coupled with a multi-family house characterized by transmittance values of the building envelope compliant with those imposed by Italian Law. The considered building is representative of a typical Italian residential application. The feasibility of the proposed trigeneration system was investigated by using the dynamic simulation software TRNSYS in comparison to a traditional supply based on separate energy production. The analyses were performed by varying the climatic conditions and considering buildings located in three different Italian cities (Palermo, Naples and Milan), which are representative of the different climatic regions of Italy. The primary energy consumption, the equivalent carbon dioxide emissions as well as the operating costs of the proposed system were evaluated based on the simulation results according to the Italian scenario and compared with those associated to a conventional system composed of a natural gas-fired boiler coupled with the same air-cooled water electric chiller fed by the electric grid. The performed analyses allowed to assess the energy, environmental and economic suitability of the proposed scheme as well as its potential benefits in comparison to the reference plant based on separate energy production.